Selective Serotonin Reuptake Inhibitor Antidepressant Treatment Discontinuation Syndrome: A Review of the Clinical Evidence and the Possible Mechanisms Involved - Renoir, Thibault (Frontiers in Pharmacology, 2013)
Besides demonstrated efficacy, selective serotonin reuptake inhibitors (SSRIs) hold other advantages over earlier antidepressants such as greater tolerability and a wider range of clinical applications. However, there is a growing body of clinical evidence which suggests that SSRIs could, in some cases, be associated with a withdrawal reaction upon cessation of regular use. In addition to sensory and gastrointestinal-related symptoms, the somatic symptoms of the SSRI discontinuation syndrome include dizziness, lethargy and sleep disturbances. Psychological symptoms have also been documented, usually developing within 1-7 days following SSRI discontinuation. The characteristics of the discontinuation syndrome have been linked to the half-life of a given SSRI, with a greater number of reports emerging from paroxetine compared to other SSRIs. However, many aspects of the neurobiology of the SSRI discontinuation syndrome (or SSRI withdrawal syndrome) remain unresolved. Following a comprehensive overview of the clinical evidence, we will discuss the underlying pathophysiology of the SSRI discontinuation syndrome and comment on the use of animal models to better understand this condition.